Mothers Knowledge and Attitude about Neonatal Jaundice in Rural Areas of Sargodha (Medical Forum Monthly, 2020)
Objective: To determine the knowledge and attitude towards symptoms, causes and prevention of neonatal jaundice among mothers in rural areas of District Sargodha.Study Design: Observational / cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Pediatrics, Rai Medical College, Doctors Trust Teaching Hospital Sargodha from 1st April 2018 to 30th September 2018.Material and Methods: A total of 115 mothers from rural areas of Sargodha were participated and interviewed in this study. The study duration was of six months. The exclusion criteria were all females with no successful pregnancy whereas all married females that delivered at least one live baby were included.Results: The mean age of the mothers was 28.2±7.6 years. We observed, 48 out of 115 (41.7%), females were below 25 years of age, whereas 55 (47.8%) were between 26-35 and 12(10.4%) were above 35 years of age. 70 (60.8%) females were with education below primary and 45 (39.2%) were above primary level of education. The first or second ranked neonates were observed in 75 (65.2%) females. We observed that 35% of females had, moderate knowledge of all symptoms related to jaundice whereas 55% were with little knowledge or not fully aware of jaundice symptoms.Conclusion: The knowledge and attitude aspects, about neonatal jaundice, of mothers were insufficient.